Brivaracetam and rufinamide combination increased seizure threshold and improved neurobehavioral deficits in corneal kindling model of epilepsy - Awais Sattar; Zohabia Rehman; Hammad Murtaza; Waseem Ashraf; Tanveer Ahmad; Faleh Alqahtani; Imran Imran (Animal Models and Experimental Medicine)
Abstract Background Besides seizures, a myriad of overlapping neuropsychiatric and cognitive comorbidities occur in patients with epilepsy, which further debilitates their quality of life. This study provides an in‐depth characterization of the impact of brivaracetam and rufinamide individually and in combination at 10 and 20 mg/kg doses, respectively, on corneal kindling‐induced generalized seizures and behavioral alterations. Furthermore, observed convulsive frequency and behavioral changes were correlated to post‐kindling‐induced changes in the activity of markers of oxidative stress. Methods Adult C57BL/6 mice were kindled via twice‐daily transcorneal 50‐Hz electrical stimulations (3 mA) for 3 s for 12 days until animals reached a fully kindled state. After the kindling procedure, animals were tested using a set of behavioral tests, and neurochemical alterations were assessed. Results Corneal‐kindled animals exhibited intense generalized convulsions, altered behavioral phenotypes typified by positive symptoms (hyperlocomotion), negative symptoms (anxiety and anhedonia), and deficits in semantic and working memory. BRV 10 + RFM 20 dual regime increased convulsive threshold and propensity toward the start of stage 4–5 seizures and improved phenotypical deficits, that is, anxiety, depression, and memory impairments. Moreover, this combination therapy mitigated kindling‐induced redox impairments as evidenced by reduced malondialdehyde and acetylcholinesterase levels and increased glutathione antioxidant activity in the brain of animals subjected to repetitive brain insult. Conclusion Based on our outcomes, this dual therapy provides supporting evidence in alleviating epilepsy‐induced neurobehavioral comorbidities and changes in redox homeostasis.